THE IMPACT OF GENERATIVE AI ON BUSINESS CONTENT CREATION AND CORPORATE COMMUNICATION - Sedoshkin, Ilia (Global Prosperity, 2025)
Abstract. The article explores how generative artificial intelligence influences business content creation and the development of corporate communication within the context of digital transformation in modern organizations. The purpose of the study is to identify emerging technological trends in the evolution of generative AI and to outline practical cases of its integration into business environments. The research employed general scientific methods of cognition: analysis, synthesis, induction, deduction, systematization, generalization, and comparative analysis, which ensured a comprehensive approach to studying the trends of generative AI application in the corporate sector. The findings indicate that 78% of companies have already implemented AI in their processes, while total investments in this field have surpassed 100 billion dollars. The study reveals that the greatest impact of this technology is observed in marketing, sales, product development, and finance, where it enhances efficiency, decision-making speed, and the accuracy of business communication. The key areas of advancement have been identified as agentic AI, AI governance, spatial computing, and polyfunctional robotics, which reshape the paradigm of human–digital interaction. The research proves that the combination of generative AI with telepresence and spatial computing technologies fosters more natural and empathetic communication capable of reproducing the emotional context of interaction. At the practical level, leading companies have already integrated generative AI into their operations: Microsoft employs Copilot for automated content creation and analytics, the communications agency Hard Numbers utilizes GPT-4, Fireflies, and Adobe Firefly, while the startup WeHead Inc., led by O. Sedoshkin, implements holographic telepresence technologies. These cases reflect a transition toward a model of cognitive partnership between humans and artificial intelligence, in which AI acts as a co-creator of meaning, trust, and emotional authenticity, marking the beginning of a new era in corporate communication. The practical significance of this study lies in identifying effective directions for using generative AI to enhance the productivity, ethics, and personalization of business communication.